Molecular characterization of clinical and environmental carbapenem resistant Acinetobacter baumannii isolates in a hospital of the Eastern Region of Saudi Arabia - Arif Al-Hamad; Tibor Pal; Hussam Leskafi; Hussein Abbas; Heba Hejles; Fatimah Alsubikhy; Dania Darwish; Akela Ghazawi; Agnes Sonnevend (Elsevier, 2020)
Background: Environmental and clinical carbapenem-resistant Acinetobacter baumannii (CRAb) isolated in a hospital of the Eastern Region of Saudi Arabia were compared to assess the potential environmental contamination by this pathogen. Methods: Frequent-hand-touch surfaces of intensive care (ICU), medical (MW), and surgical (SW) units were randomly sampled for a month-long period, and the CRAb identified were compared to clinical isolates of the same period by PFGE and blaOXA-51-like gene sequencing. Carbapenemase and ribosomal methylase genes, ISAba1 link to blaOXA51-like or to blaOXA-23, respectively were detected by PCR. Results: CRAb was identified from 35.5% of surfaces. All environmental and clinical isolates were multi- or extremely drug resistant. PFGE of all clinical (n = 21) and selected environmental (n = 30) isolates identified a singleton and four clusters, all of which included both clinical and environmental isolates. In the two largest clusters isolates carried blaOXA-66, ISAba1-linked blaOXA-23, and were from the ICU, MW and the male SW. Isolates of the female SW carried blaOXA-69, ISAba1-linked blaOXA-23 and blaGES-11. A pair of clinical and environmental CRAb from the Male SW harboured blaNDM-1 in addition to ISAba1-linked blaOXA-94. Conclusion: A worrying level of environmental contamination, often by CRAb belonging to international clones, was revealed, highlighting the importance of environmental hygiene. Keywords: Acinetobacter baumannii, Multidrug resistance, Environmental contamination, Molecular typing